Assessment of PTSD and posttraumatic symptomatology in very young children: A systematic review. - Moner, Nina; Soubelet, Andrea; Barbieri, Lucrezia; Askenazy, Florence (Journal of Child & Adolescent Psychiatric Nursing, 2022)
Context: Very young children are said to be a vulnerable group for exposure to trauma, and for a psychopathological response (e.g., PTSD) after a risk‐exposure. The specific assessment of young children is necessary to enable them to be enrolled in an appropriate care pathway. Objective: The objective was to identify the instruments available in the English language for the assessment of posttraumatic symptoms in very young children (from 0‐ to 5‐year old). Design: This article reports on a systematic review, conducted using the search engines Google Scholar, Science Direct, PsycArticles, and PubMed. Results: Nine instruments are available to specifically assess traumatic symptomatology in very young children (0–7‐year old), five instruments are available for the broader assessment of very young children (1–6‐year old), six instruments are available for the assessment of traumatic symptoms in very young children and in older children (2–18‐year old), one instrument did not correspond to any category. These 21 tools are adapted to different ages, built according to different objectives, and do not rely on the same diagnostic algorithm. Conclusion: Future research should compare the instruments quantitatively to identify those most specific and sensitive to the assessment of trauma symptoms in young children.